The effect of pre-eclampsia on retinal microvascular caliber at delivery and post-partum. (September 2018) - Soma-Pillay, P; Pillay, R; Wong, TY; Makin, JD; Pattinson, RC
Background: The retinal microcirculation provides a unique view of microvessel structure by means of non-invasive, retinal image analysis. The aim of the study was to compare the retinal vessel caliber at delivery and one-year post-partum between women who have had pre-eclampsia during pregnancy to a normotensive control group. Methods: Digital photos of the eye were taken at delivery and one-year post-partum. Retinal vessels were analysed and summarised as the corrected central retinal arteriolar equivalent and corrected central retinal venular equivalent. Results: The corrected central retinal arteriolar equivalent and corrected central retinal venular equivalent were significantly lower in the pre-eclamptic group compared to the control group both at delivery and one-year post-partum ( p < 0.001). Conclusion: Retinal artery and venular caliber changes that occur during pregnancies affected by pre-eclampsia persist for up to one-year post-partum. These changes may reflect a permanent, long-term microvascular dysfunction and may be useful as a biomarker of future vascular risk.